Alberuni’s India : an account of the religion, philosophy, literature, geography, chronology, astronomy, customs, laws and astrology of India about A. D. 1030 - Biruni, Ebu’r-Reyhan Muhammed b. Ahmed, 973-1061? (New Delhi, Chennai)
2 c.